2011
DOI: 10.1002/dneu.20944
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial membrane transporters expression in the developing to adult mouse vomeronasal organ and olfactory mucosa

Abstract: To contribute clarifying mechanisms operating in nose chemosensory epithelia and their developmental patterns, we analyzed the expression of different epithelial membrane transporters as well as the Clara cell secretory protein, CC26 in the olfactory, vomeronasal organ (VNO), and respiratory epithelia of embryonic (E13-E19) and postnatal (P1-P60) mice by means of immunohistochemistry and reverse transcriptase-polymerase chain reaction. Results showed that CC26, cAMP-activated chloride channel (CFTR), and the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
0
9
1
Order By: Relevance
“…To this end, we first performed in situ hybridization and immunohistochemistry analysis to locate CFTR in mouse OE. Unlike published results, which tentatively localized CFTR mRNA in sustentacular cells (Merigo et al, ), we observed that CFTR is selectively expressed by CD73‐positive microvillar cells. Therefore, we systematically assessed the role of CFTR in microvillar cells for the regulation of olfactory homeostasis, using CFTR‐knockout mice and their wildtype littermates for comparison.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…To this end, we first performed in situ hybridization and immunohistochemistry analysis to locate CFTR in mouse OE. Unlike published results, which tentatively localized CFTR mRNA in sustentacular cells (Merigo et al, ), we observed that CFTR is selectively expressed by CD73‐positive microvillar cells. Therefore, we systematically assessed the role of CFTR in microvillar cells for the regulation of olfactory homeostasis, using CFTR‐knockout mice and their wildtype littermates for comparison.…”
contrasting
confidence: 99%
“…A previous study reported possible CFTR expression by sustentacular cells in the murine OE (Merigo et al, ). Here, we used the microvillar cell‐specific marker CD73 (Pfister et al, ) to prove CFTR expression and localization in microvillar cells.…”
Section: Discussionmentioning
confidence: 87%
“…CFTR plays a crucial role in maintaining the salt and water balance of mucosal secretions and is widely expressed in the nasal epithelia (Grubb et al 2007;Rochelle et al 2000). A notable exception is the Bowman's gland (Merigo et al 2011). In the absence of CFTR, Ca 2+ -activated Cl − channels can act as a substitute in mucosal secretion (Kidd and Thorn 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Expression of AQP4 was identified in the animal's olfactory, visual, and auditory organs. Expression of AQP4 was observed in olfactory epithelium, retina, and the optic nerve in rats . AQP4 was expressed in sensory organs and in the mammalian brain.…”
Section: General Characteristics Of Aquaporinsmentioning
confidence: 98%